Assessment of Gap between Knowledge and Practices among Type 2 Diabetes Mellitus Patients at a Tertiary-Care Hospital in Bangladesh - Farzana Saleh; Ferdous Ara; Fadia Afnan (Advances in Public Health)
Newly diagnosed type 2 diabetes (T2 DM) patients who do not receive diabetes education (DE) have average knowledge on DM, and their practices about diabetes need to be improved. This prompted us to evaluate what happens when old diagnosed patients receive DE. The study therefore assessed the association between knowledge and practices in terms of Hemoglobin A1c (HbA1c), body mass index (BMI), and waist circumference (WC) among 500 diagnosed T2 DM using a cross-sectional design. An interviewer-administered questionnaire was used for assessing their knowledge. The mean knowledge score of the patients was 15.29 ± 3.6. A significant negative association was found between the knowledge score and the HbA1c level. Age was positively associated with HbA1c and WC. Duration of DM was positively and education was negatively associated with HbA1c. Gender was negatively associated with BMI while income was positively associated with BMI and WC. All the associations were significant. The diagnosed T2 DM patients are deficient of sufficient knowledge; the knowledge score and HbA1c have a significant negative relationship, not other actions. The risk factors for the patients’ outcome include old age, female gender, years of education, economic status, and duration of DM.